THE EFFECTIVENESS OF LISTEN-DISCUSS STRATEGY (LRD) TOWARD READING STUDENTS’ COMPREHENSION - Eka Pebriana; Sisca Wulansari Saputri; Aa Qonaatun (Journal of English Language Teaching and Literature (JELTL), 2019)
This research uses of Listen Read Discuss strategy in reading comprehension. This research was conducted based on formulation of the problem. The objective of this research was to know whether there was any significant effect of using Listen Read Discuss Strategy (LRD) strategy toward reading students’ comprehension at the eighth grade of MTS Nurul Falah Kresek. The writer used quantitative research by using quasi experimental research method. Class VIII B as the experimental group which was consisted of 20 students, class VIII A as the control group which was consisted of 20 students. The data were collected by reading test. It can be seen from the result pretest and post-test in experimental and control class. The writer analyzed by using t-test. The result of this research revealed that the post-test scores were better than the pre-test scores. It can be seen from the result of t-test. The criteria of two tailed test with significance level (α = 0.05 ) was T table ≤ T test ≤ T table: H0 is rejected and Ha is accepted. The result of computation got T test = 3.226 and T table = 0.444. It means 0.444 < 3.226 > 0.444. H0 is rejected and Ha was accepted. Based on the conclusion above, it can be concluded that reading comprehension through LRD strategy was more effective for increasing reading comprehension. There is the differences of the teaching learning process between two classes. In the other words, students’ reading comprehension that were taught through LRD strategy was higher than those who were not through LRD strategy.